2008
DOI: 10.4049/jimmunol.181.6.3804
|View full text |Cite
|
Sign up to set email alerts
|

MyD88 Plays a Critical T Cell-Intrinsic Role in Supporting CD8 T Cell Expansion during Acute Lymphocytic Choriomeningitis Virus Infection

Abstract: During acute lymphocytic choriomeningitis virus (LCMV) infection, CD8 T cells rapidly expand and differentiate into effectors that are required for viral clearance. The accumulation of activated T cells is greatly reduced in mice lacking the adaptor molecule MyD88. Although MyD88 has generally been considered to indirectly regulate adaptive immune responses by controlling inflammatory cytokine production and Ag presentation in innate immune cells, in this study, we identify an unappreciated cell-intrinsic role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
88
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(105 citation statements)
references
References 31 publications
17
88
0
Order By: Relevance
“…Using adoptive transfer systems, we and others have previously shown that MyD88 expression in T cells is critical for regulating the size of the resulting memory population after acute viral infection. [4][5][6] Our initial experiments with T cell-specific Myd88-deficient mice confirmed these observations, showing that in the absence of MyD88 expression in T cells, LCMV infection induced significantly smaller populations of effector and memory cells. We further confirmed these results using cKO mice in which tamoxifen treatment deletes MyD88 expression before viral infection.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Using adoptive transfer systems, we and others have previously shown that MyD88 expression in T cells is critical for regulating the size of the resulting memory population after acute viral infection. [4][5][6] Our initial experiments with T cell-specific Myd88-deficient mice confirmed these observations, showing that in the absence of MyD88 expression in T cells, LCMV infection induced significantly smaller populations of effector and memory cells. We further confirmed these results using cKO mice in which tamoxifen treatment deletes MyD88 expression before viral infection.…”
Section: Discussionsupporting
confidence: 67%
“…We found that the majority of YFP ϩ cells in cKO mice still lacked MyD88 expression, indicating that the memory T-cell response in cKO mice did not merely reflect preferential expansion of MyD88-sufficient cells ( Figure 6D). Because we have previously reported increased apoptosis in Myd88 Ϫ/Ϫ effector cells during primary expansion in response to LCMV, 6 we also examined the survival of LCMV-specific T cells after secondary expansion. Consistent with their comparable expansion, we found no notable differences in the apoptosis of YFP ϩ np396-specific cells in cKO and cHet mice either directly ex vivo or after in vitro culture ( Figure 6E).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, NKT cells may be affected directly, through TCR recognition of foreign-lipid Ags presented by CD1d molecules on the surface of an APC (18,19,(41)(42)(43), or indirectly, via presentation of endogenous lipids and production of cytokines, such as IL-12 and IL-18, by APCs upon TLR-induced activation (44,45). It is also possible that NKT cells may be directly activated through cell-intrinsic recognition of TLR agonists, a phenomenon recently suggested for conventional CD8 T cells (46). That heat-killed M. tuberculosis is the active component of CFA and contains several TLR2 agonists (47,48) suggests that CFA may activate NKT cells through a TCRindependent, TLR-dependent pathway.…”
Section: Nkt Cell Activation By Cfa Is Independent Of Myd88mentioning
confidence: 99%
“…However, a strong innate immune response is important for the generation of an effective adaptive response against viral infections (Jung, Kato et al 2008;Rahman, Cui et al 2008;Zucchini, Bessou et al 2008). Moreover, DCs are indispensible for the generation of the CD8+ effector T cells.…”
Section: Chronic Viral Infections Inhibit Innate and Dendritic Cell Rmentioning
confidence: 99%